(untitled) (Theological Kronos, 2020)
Motivated by a personal experience of sexual abuse, the author addresses the problem that affects many people, mostly women. Initially, it exposes the alarming figures in Colombia and the consequences on a physical, psychological and spiritual level. Then, she raises three ways for the transformation of these traumatic experiences through the approach to the truth of the word of God and a relationship with Him, psych-spiritual care in counseling, psychological therapy and non-professional helping relationships and finally in the approach to symbolic expressions such as art, games and literature.